The Accordion in the Americas : Klezmer, Polka, Tango, Zydeco, and More! - Simonett, Helena (Book collections on Project MUSE., 2012)
This collection considers the accordion and its myriad forms, from the concertina, button accordion, and piano accordion familiar in European and North American music to the exotic-sounding South American bandoneón and the sanfoninha. Capturing the instrument's spread and adaptation to many different cultures in North and South America, contributors illuminate how the accordion factored into power struggles over aesthetic values between elites and working-class people who often were members of immigrant and/or marginalized ethnic communities. Specific histories and cultural contexts discussed include the accordion in Brazil, Argentine tango, accordion traditions in Colombia, cross-border accordion culture between Mexico and Texas, Cajun and Creole identity, working-class culture near Lake Superior, the virtuoso Italian-American and Klezmer accordions, Native American dance music, and American avant-garde.